Prevalence and associated risk factors of Tension-Type Headache among adults aged 19-50 in Rawalpindi and Islamabad, Pakistan - Muhammad Sheraz Ali; Shahzaib ud din Hamza; Habib Ullah; Waqar Ahmed; Muhammad Saddam Nawaz (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Tension-Type Headache (TTH) is the most common primary headache disorder, with prevalence rates in the general population ranging between 30% and 78%. As the second most prevalent medical condition, TTH can be significantly disabling. The variation in prevalence is influenced by factors such as age, background, environment, and education level. Diagnosis of TTH primarily relies on criteria including repeated headache episodes lasting from 30 minutes to 7 days, characterized by bilateral, mild-to-moderate pressing or tightening pain that is not aggravated by daily activities. Purpose: This study aimed to determine the prevalence of TTH and identify associated risk factors within the adult population of Rawalpindi and Islamabad, Pakistan, where limited data is available. Methods: A cross-sectional descriptive study was conducted with 385 participants aged 19-50. Using non-probability convenience sampling, data was gathered from the general population of Rawalpindi and Islamabad through headache screening questionnaires and demographic surveys. The study analyzed factors such as sleep quality, blood pressure, hormonal fluctuations, stress, and depression using odds ratios (OR) and other statistical measures in SPSS. Results: Of the 385 participants (mean age: 27.19 years; 50.91% male), 78.44% were diagnosed with TTH, with 21.04% reporting infrequent TTH, 70.91% frequent TTH, and 8.05% chronic TTH. Key associated risk factors included insufficient sleep (OR = 1.272), high blood pressure (OR = 1.301), neck muscle pain (OR = 1.094), disturbed sleep (OR = 1.062), stress (OR = 1.658), and depression (OR = 1.329). Other factors, such as smoking, poor posture, and missed meals, were not significantly associated with TTH. Conclusion: TTH is a prevalent yet often overlooked condition with modifiable risk factors including sleep disturbance, high blood pressure, stress, and depression. The findings underscore the need for targeted interventions to manage TTH risk factors, which could improve quality of life and reduce the disability burden associated with TTH in this population. Keywords: Tension-Type Headache (TTH); Prevalence of TTH; Associated Risk Factors; Adult Headache Disorders; Rawalpindi and Islamabad; Sleep Disturbance and Hypertension.